PENGEMBANGAN E-LKPD BERBANTUAN WIZER.ME PADA TOPIK SEPERTI APAKAH BUDAYA DAERAHKU? MATA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL - Abas Husen; Yuyun Elizabeth Patras; Dita Destiana (STKIP Subang, 2026)
This research aims to develop and test the feasibility and effectiveness of interactive E-LKPD assisted by Wizer.me as a solution to the low student motivation caused by the use of monotonous conventional LKPD. This research uses the research and development (R&D) method with the ADDIE model. The research subjects involved three expert validators, a teacher, and 30 fifth-grade students from SDN Citayam 1. Data were collected through validation sheets, user response questionnaires, and learning outcome tests (pre-test and post-test). The research results show that the developed product is deemed highly suitable for use, with an average expert validation score of 96%. User responses were also very positive, with scores of 84% from teachers and 91% from students. The product's effectiveness in improving learning outcomes was proven to be high, with an N-Gain score of 0.71. It is concluded that the Wizer.me-assisted E-LKPD is a valid, practical, and effective learning medium to enhance student motivation and learning outcomes in IPAS education at elementary schools.